Integration of a modified double-infinite Toda lattice by using the inverse spectral problem - Berezansky, Yu. M. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
An approach to finding a solution of the Cauchy problem for a modified double-infinite Toda lattice by using the inverse spectral problem is given.